Investigating the effect of sodium bicarbonate solution on onset and duration of anesthesia with the use of adrenaline solution in surgical patients undergoing epidural anesthesia - Vakilian, G (Iran University of Medical Sciences, 1995)
In this quasi-experimental study, we assess the effect of sodium bicarbonate solution on onset and duration of anesthesia with the use of lidocaine and adrenaline solution in surgical patients undergoing epidural anesthesia